1995
DOI: 10.1007/bf00873688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth conditions on mitochondrial morphology inSaccharomyces cerevisiae

Abstract: Effects of growth conditions on mitochondrial morphology were studied in living Saccharomyces cerevisiae cells by vital staining with the fluorescent dye dimethyl-aminostyryl-methylpyridinium iodine (DASPMI), fluorescence microscopy, and confocal-scanning laser microscopy. Cells from respiratory, ethanol-grown batch cultures contained a large number of small mitochondria. Conversely, cells from glucose-grown batch cultures, in which metabolism was respiro-fermentative, contained small numbers of large, branche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 37 publications
3
74
0
Order By: Relevance
“…The strain BY4743 (24) used in this study exhibits relatively simple mitochondrial networks on fermentable carbon sources like glucose, whereas on nonfermentable sources such as glycerol, the network is branched and more elaborate. Although straindependent differences have been reported (25), this appears to be a typical behavior.…”
Section: Multifocal Multiphoton 4pimentioning
confidence: 72%
See 1 more Smart Citation
“…The strain BY4743 (24) used in this study exhibits relatively simple mitochondrial networks on fermentable carbon sources like glucose, whereas on nonfermentable sources such as glycerol, the network is branched and more elaborate. Although straindependent differences have been reported (25), this appears to be a typical behavior.…”
Section: Multifocal Multiphoton 4pimentioning
confidence: 72%
“…To demonstrate its continuous reticular structure, Nunnari et al (30) have gained 3D images of the mitochondrial compartment by means of epifluorescence microscopy combined with image restoration. This method, as well as confocal fluorescence microscopy (25), allowed a distinction of glycerol-and glucosegrown yeast cell populations. However, in both cases, the limited spatial resolution rendered an equilateral 3D representation of the mitochondrial compartment impossible.…”
Section: Multifocal Multiphoton 4pimentioning
confidence: 99%
“…During ageing in CR and SCG the mitochondria appear progressively more numerous and present a clear spherical shape. Even the mitochondria morphology of SCD grown cells tends to become similar to the one in CR and SCG by passing to the derepressed state characteristic of low glucose level [32], although some cells tend to Research Article 937 retain mitochondria with filamentous morphology. It is interesting to note that the number of GFP-labelled yeast cells drastically decreased during ageing in SCD compared to the other two conditions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…This increase was related to the mitochondria state [38,39]. During the exponential phase and even more so during ageing, cells grown in CR or SCG displayed small and numerous mitochondria; these differences were previously analysed by Visser [32], who shows that the reticular morphology is associated with a repressed condition typical of growth in high glucose medium or oxygen absence, whereas yeast cells growing on non-fermentable carbon sources display a large number of small mitochondria. This situation is not reproducible in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…This yeast dramatically regulates the shape, size, and number of its mitochondria during cell growth [3]. It was found that the number of mitochondria increases when cells of Saccharomyces cerevisiae are under glucose-limiting conditions [4].…”
Section: Introductionmentioning
confidence: 99%